ANALISIS YURIDIS PENYELENGGARAAN MEDIASI MENURUT HUKUM POSITIF DI INDONESIA - Heriyanti, Yuli; Zikri, Ahmad (Pahlawan Tuanku Tambusai University, 2024)
The court's authority to resolve civil disputes is based on the Trias Politika doctrine, giving rise to the stigma that the court is